Call the midwife. Season eleven [videorecording (DVD)] - Thomas, Heidi, 1962- (BBC Studios, 2022)
1967 brings fresh medical and personal challenges to the midwifery and district nursing rounds. Thanks to Matthew's continued support, things at Nonnatus House are now settled and going well, and Trixie helps Matthew understand the community he is becoming a part of. Doctor Turner faces some changes in his relationship with Timothy now that he is an adult, while Shelagh continues to support community health programs. Across the series, the team faces challenging situations concerning addiction, a baby with a life-threatening condition, breastfeeding difficulties, and a Holocaust survivor.